Pengukuran Tingkat Kepuasan Mahasiswa Terhadap Layanan Di Prodi Informatika Universitas Dehasen Bengkulu - Safrawi Waruwu; Dewi Suranti; Eko Suryana (Jurnal Media Infotama, 2026)
Excellent service is a crucial aspect of commercial success, especially in service organizations. Excellent service is the spearhead in seizing opportunities and understanding consumers or clients who will use the services offered. To produce quality graduates, one of the influencing factors is the service implemented within the faculty environment in serving customers, in this case students. Satisfaction with academic services is something that needs to be considered in order to achieve quality services that guarantee student satisfaction as the main stakeholder in educational service organizations. This study aims to determine the level of student satisfaction with the quality of service in the Informatics Study Program at Dehasen University, Bengkulu. From the results of the testing conducted, the Student Satisfaction Level Measurement System for Services in the Informatics Study Program at Dehasen University, Bengkulu has been able to assist in making service decisions for the Informatics Study Program at Dehasen University, Bengkulu.